Pattern recognition in bioinformatics : second IAPR international workshop, PRIB 2007, Singapore, October 1-2, 2007 : proceedings - Rajapakse, Jagath Chandana; Schmidt, Bertil; Volkert, Gwenn; SpringerLink (Online service) (New York : Springer, 2007)
Includes bibliographical references and index